DEVELOPING TEACHERS’ COMPETENCIES IN DIGITAL MEDIA PRODUCTION FOR LEARNING MANAGEMENT AT PHETCHABURI VOCATIONAL COLLEGE UNDER THE OFFICE OF THE VOCATIONAL EDUCATION COMMISSION - Jantaros, Arunkamol; Lenanant, Apichat (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
This research aimed at 1) assessing the needs for developing teachers’ competencies in digital media production for learning management at Phetchaburi Vocational College (PBIVC), 2) creating a training course for enhancing teachers’ competencies in digital media production for learning management, 3) developing teachers’ competencies in digital media production for learning management; and 4) monitoring, evaluating, and reflecting on the development of teachers’ competencies in digital media production for learning management. The target group for this research consisted of 66 teachers at PBIVC in the 2023 academic year, selected through purposive sampling. The research instruments comprised a set of questionnaires, a course evaluation form, a digital media evaluation form, and a reflection interview form. The Index of Item–Objective Congruence (IOC) ranged from 0.80 to 1.00. Statistical analyses included frequency, percentage, mean, and standard deviation. Research results were as follows: 1) The needs assessment for developing teachers’ competencies in digital media production for learning management revealed that the demand for improved digital media production skills was at the highest level, 2) The training course development designed to enhance teachers’ competencies in digital media production for learning management indicated that the structure of the training workshop course integrated both theoretical and practical components, with a total duration of eight hours. The evaluation of the training course was rated overall at the highest level, 3) The implementation of the teachers’ competencies in digital media production for learning management revealed that teachers gained knowledge, skills, and experience in producing digital teaching media, and applied their knowledge in creating educational materials. The evaluation of digital media for learning management was rated overall at the highest level, and 4) The results from evaluating and reflecting on the development of teachers’ competencies in digital media production for learning management indicated that teachers applied knowledge, skills, and experience acquired to produce digital media for instructional purposes.The created digital media were aligned with the content and modernized for learning management, enabling students to access digital media anywhere and anytime. This flexibility supported students’ learning and prompted teachers to seek further development in the use of technology for learning management in the future.